Imaging and structural studies of DNA–protein complexes and membrane ion channels. Issue 8 (3rd February 2017) - Marini, M.; Limongi, T.; Falqui, A.; Genovese, A.; Allione, M.; Moretti, M.; Lopatin, S.; Tirinato, L.; Das, G.; Torre, B.; Giugni, A.; Cesca, F.; et al.
Abstract : A unified preparation method based on super-hydrophobicity for TEM imaging and structural studies of biological systems from DNA to membranes. Abstract : In bio-imaging by electron microscopy, damage of the sample and limited contrast are the two main hurdles for reaching high image quality. We extend a new preparation method based on nanofabrication and super-hydrophobicity to the imaging and structural studies of nucleic acids, nucleic acid–protein complexes (DNA/Rad51 repair protein complex) and neuronal ion channels (gap-junction, K + and GABAA channels) as paradigms of biological significance and increasing complexity. The preparation method is based on the liquid phase and is compatible with physiological conditions. Only in the very last stage, samples are dried for TEM analysis. Conventional TEM and high-resolution TEM (HRTEM) were used to achieve a resolution of 3.3 and 1.5 Å, respectively. The EM dataset quality allows the determination of relevant structural and metrological information on the DNA structure, DNA–protein interactions and ion channels, allowing the identification of specific macromolecules and their structure.